Biocompatible polymer blends of poly(D,L-lactic acid-co-glycolic acid) and triblock PCL-PDMS-PCL copolymers: Their characterizations and degradations - (:unkn) unknown (CROATIAN CHEMICAL SOC, 2004)
Polymer blends of poly(D,L-lactic-co-glycolic acid), PDLLGA, and triblock polycaprolactone-poly(dimethylsiloxane)-polycaprolactone (PCL-PDMS-PCL) copolymer, TEGOMER, were obtained by coprecipitation from their chloroform mixed solutions into methanol and were characterized by differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), degradation tests and scanning electron microscopy (SEM). Binary blends of PDLLGA/TEGOMER were found to be partially miscible according to DSC measurements and FTIR analysis. Stress-strain results showed that addition of TEGOMER improved significantly the overall toughness of PDLLGA. Degradation of PDLLGA/TEGOMER blends was investigated in phosphate buffered saline at pH = 7.4 and 37degreesC, and the morphology of the blends during degradation was examined by scanning electron microscopy.
Keywords: poly(D,L-lactic acid-co-glycolic acid; polycaprolactone-poly(dimethyl-siloxane)-polycaprolactone; degradation; blends; ENANTIOMERIC POLY(LACTIC ACID)S; STEREOCOMPLEX FORMATION; IN-VITRO; CRYSTALLIZATION; SCAFFOLDS; DELIVERY; CAST